The Potential Of Moringa Oleifera (Kelor) And Cerbera Odollam (Pong-Pong) Waste Oil Extraction As Locusts Elimination - Muhamad Shahirul Faiz, Mohd Nasir (2022)
Locusts is one of the primary issues in agriculture industries causing major crop failure. Frequent outbreaks have led to tremendous environmental and economic losses. The chemical pesticides employed in most agriculture retain some negative impact on non-target organisms and environmental contamination. Botanical pesticides or commonly known as biopesticides is one of the alternatives to overcome this problem. Thus, the potential of moringa oleifera and cerbera odollam extraction to use as biopesticides in elimination of locusts was studied in this current research. The seeds from moringa and leaves from cerbera was prepared to extract using ethanol extraction process. The oil extraction products were investigated into a number of locusts for 150 min observation period. The amount of locust survived were calculated for every 15 min. Both moringa and cerbera recorded 100% mortality rate. The plants and grass maintain its condition inside the locust’s storage throughout this observation period. Macro and micro elements in the moringa extract help to protect the plant and environment but also acts as efficient biopesticides. Meanwhile, cerbera leaves is rich with flavonoids, saponins, cerberin and alkaloids compound and therefore, beneficial to eliminate locusts. Moringa oils recorded pH of 6.81 whereas, cerbera oils recorded pH of 6.82. The pH for both oils closer to natural 7 extend its confirmation of environmentally-friendly attributes. Cerbera oil recorded faster time to eliminate all 30 locusts credited its high absorption rate. The presence of multiple compounds was confirmed based on FTIR analysis on moringa and cerbera oil such as alcohol and hydroxyl, alkanes, tertiary amines, aromatic amines, C-O group and C-H group of alkenes. Both extraction oils are regarded beneficial and effective credited to several advantages, namely, eco-friendly, cost-friendly, simple preparation method with high mortality rate of locusts.